2010
DOI: 10.1080/17470211003660501
|View full text |Cite
|
Sign up to set email alerts
|

Context Effects in Auditory Implicit Memory

Abstract: The context effect in implicit memory is the finding that presentation of words in meaningful context reduces or eliminates repetition priming compared to words presented in isolation. Virtually all of the research on the context effect has been conducted in the visual modality but preliminary results raise the question of whether context effects are less likely in auditory priming. Context effects in the auditory modality were systematically examined in five experiments using the auditory implicit tests of wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…Interestingly, although Hebrew speakers performed consistently in both modalities, English speakers performed better in the auditory condition. The Hebrew speakers' performance is similar to that reported by Besken and Mulligan () and Brand and Jolles (), whose results demonstrated similar performance in visual and auditory modalities.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Interestingly, although Hebrew speakers performed consistently in both modalities, English speakers performed better in the auditory condition. The Hebrew speakers' performance is similar to that reported by Besken and Mulligan () and Brand and Jolles (), whose results demonstrated similar performance in visual and auditory modalities.…”
Section: Discussionsupporting
confidence: 88%
“…The study aimed to investigate the interaction between CE as elicited by the consistency of language of presentation (Hebrew vs. English), with native language (Hebrew vs. English), in both auditory and visual modalities. Although previous studies have already demonstrated the CE of modality of presentation (Besken & Mulligan, 2010;Loveman et al, 2002;Vakil et al, 1997), this is one of the first studies to examine the relationships between these variables simultaneously (i.e., consistency of language of presentation, native language, and modality).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The CINET is inspired by the context effect, which is the influence of the surrounding environment on the perception of stimuli [1][2][3]. Numerous studies related to the context effect have shown that the integration of contextual information improves the interpretation of spoken words [4,5], written letters and words [6][7][8], physical objects [9][10][11], sounds [12,13], smells [14], tastes [15], threats [16], colors [17], and facial emotions [18][19][20]. The context effect has also been widely studied to show how contextual information is used to uniquely resolve the interpretation of ambiguous stimuli [7,8,[21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%